CRISPR/Cas9-mediated multiple gene editing in Brassica oleracea var. capitata using the endogenous tRNA-processing system. Issue 1 (1st February 2019) - Ma, Cunfa; Zhu, Chenzeng; Zheng, Min; Liu, Mengci; Zhang, Dejun; Liu, Baoli; Li, Qinfei; Si, Jun; Ren, Xuesong; Song, Hongyuan
Abstract: Cabbage ( Brassica oleracea var. capitata ) is a biennial plant with strong self-incompatibility and an obligate requirement for prolonged vernalization by exposure to low temperatures to induce flowering. These characteristics significantly increase the difficulty of exploiting novel germplasm induced by physical or chemical mutagens. In this study, we report a CRISPR/Cas9 gene-editing system based on endogenous tRNA processing to induce high efficiency and inheritable mutagenesis in cabbage. Using the phytoene desaturase gene BoPDS, the S-receptor kinase gene BoSRK, and the male-sterility-associated gene BoMS1 as the target genes, multisite and multiple gene mutations were achieved using a construct with tandemly arrayed tRNA-sgRNA architecture to express multiple sgRNAs. The BoSRK3 gene mutation suppressed self-incompatibility completely, converting the self-incompatible line into a self-compatible line. In addition, the BoMS1 gene mutation produced a completely male-sterile mutant, which was highly cross compatible with its nonmutant isoline at the flowering stage as a result of a simultaneous BoSRK3 gene mutation, enabling the economic propagation of the male-sterile line through bee-mediated cross-pollination. Interestingly, higher site mutation efficiency was detected when a guide sequence was inserted into a location in the tandemly arrayed tRNA-sgRNA architecture that was distal from the upstream Pol III promoter. In addition, mutation sites were also detected in the paralogous genes of the BoPDS and BoSRK genes that had fully consistent sequences or base mismatches but beyond the "seed" region in the spacer sequence compared with the target sgRNAs. Collectively, our results demonstrate that the CRISPR/Cas9 system, coupled with an endogenous tRNA-processing system, is an efficient tool to improve cabbage traits. Crop genetics: CRISPR editing of multiple genes in cabbage: Researchers in China have shown that the gene-editing system CRISPR/Cas9 can be used to efficiently mutate genes of interest in cabbage. Cabbage plants normally do not self-pollinate, making the use of traditional mutagens difficult. Hongyuan Song of Southwest University therefore turned to CRISPR/Cas9, a system which can introduce precise mutations into specific genes. Song's team targeted three genes: one related to coloration, another to self-incompatibility, and a third involved in pollen development. They began by mutating each gene separately to test the system's efficiency. Next, they built a CRISPR/Cas9 construct that would simultaneously mutate the pollen gene and the self-incompatibility gene. One-third of the plants produced using the construct had mutations in both of the target genes. These findings demonstrate that CRISPR/Cas9 is a valuable tool for trait improvement and genetic research in cabbage.